2009
DOI: 10.1051/0004-6361/200912455
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ellerman bombs due to 3D flux emergence

Abstract: Aims. We investigate the emergence of a "sea-serpent" magnetic field into the outer solar atmosphere and the connection between undulating fieldlines and formation of Ellerman bombs. Methods. We perform 3D numerical experiments solving the time-dependent and resistive MHD equations. Results. A sub-photospheric magnetic flux sheet develops undulations due to the Parker instability. It rises from the convectively unstable sub-photospheric layer and emerges into the highly stratified atmosphere through successive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
101
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 35 publications
17
101
2
3
Order By: Relevance
“…The suggested domain is significantly hotter than the relative heating obtained by Archontis & Hood (2009) in their EB simulation. However, more recent MHD simulations of comparable reconnection phenomena show larger heating (Archontis & Hansteen 2014;Lee et al 2015), likely through magnetosonic wave excitation and dissipation (Longcope & Priest 2007).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The suggested domain is significantly hotter than the relative heating obtained by Archontis & Hood (2009) in their EB simulation. However, more recent MHD simulations of comparable reconnection phenomena show larger heating (Archontis & Hansteen 2014;Lee et al 2015), likely through magnetosonic wave excitation and dissipation (Longcope & Priest 2007).…”
Section: Discussionmentioning
confidence: 57%
“…Paper I showed that at high resolution upright flame morphology in limbward viewing is a distinctive EB characteristic. It was used in Paper II to establish EB brightness criteria, but these may fail close to disk center (Paper III) where differentiation with the MCs that produce EBs (as in the serpentine U-loop pull-up scenario of EB formation of e.g., Bernasconi et al 2002;Pariat et al 2004;Isobe et al 2007;Archontis & Hood 2009;Pariat et al 2009) is less easy, as already pointed out by Ellerman (1917) and later by Bruzek & Durrant (1977).…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…The studied filament in this paper was existing for several rotations. MHD models show that the convection cells are different in flux emergence regions (Archontis & Török 2008;Archontis & Hood 2009). Future studies of the coupling between convection and filaments should be done during filament emergence.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The HMI line forms in the middle of photosphere so we have only direct evidence for a photospheric flux cancellation. The magnetic reconnection scenario also has support from numerical modeling of resistive flux emergence in the solar surface (Archontis & Hood 2009). The magnetic field strength associated with the site of the EB in our data is comparable to the values reported by Socas-Navarro et al (2006) andBello González et al (2013) who reported a field strength on the order of the equipartition value.…”
Section: Magnetic Structure Of the Ebmentioning
confidence: 85%